Outcome of corneal transplantation in a private institution in Saudi Arabia - Omar, Nazri; Bou Chacra, Charbel T.; Tabbara, Khalid F. (Dove Medical Press, 2013)
BACKGROUND: The aim of this work was to describe the indications, complications, and outcomes of penetrating keratoplasty (PKP) in Saudi Arabia. METHODS: In a retrospective, noncomparative interventional case series, the medical records of patients who underwent PKP from January 2000 to December 2008 and had a minimum follow-up of 6 months were reviewed. All corneas were obtained from eye banks in the US. Indications, complications, and outcomes of surgery were recorded. This study was approved by the institutional review board. RESULTS: Eighty-five consecutive eyes were included in this study. There were 52 (61.2%) males and 33 (38.8%) females. The median age was 35.0 years (range 3-85 years), and the median follow-up period was 24 months (range 6-108 months). The indications for PKP were keratoconus, bullous keratopathy, corneal scars, corneal dystrophy, and corneal regraft. The overall graft survival time was 88.9 months ± 4.9 months (mean ± standard error of mean, 95% confidence interval [CI] 79.4 months -98.4 months) while the 3-year and 5-year cumulative survival rates were 90.7% and 84.3%, respectively. Surgical indication (P = 0.038), immune rejection (P < 0.001), preoperative corneal vascularization (P = 0.022), and perioperative high intraocular pressure (P = 0.032) were associated significantly with corneal graft failure in univariate analysis. Multivariate analysis reduced these significant associations to rejection (P < 0.001) and vascularization (P = 0.009). Relative risk for failure in rejected cornea was 16.22 (95% CI 4.99-52.69) and in vascularized cornea was 3.89 (95% CI 1.36-11.09). At last visit following PKP, 34 (40%) eyes had best spectacle-corrected visual acuity of 20/40 or better, and 51 (60.0%) eyes had 20/80 or better. Best spectacle-corrected visual acuity was worse than 20/400 in 15 (17.6%) eyes. CONCLUSION: The overall corneal graft survival in a private setting in Saudi Arabia can be excellent. Thorough preoperative evaluation and comprehensive postoperative management are crucial for successful corneal transplantation. A larger multicenter study is recommended to portray the outcome of private corneal transplantation in Saudi Arabia in general.